The Civic Disposition of Maluku Ethnicity in Indonesian Nationalism as a Form of Civic Education - Fricean Tutuarima; Agustinus Nindatu (AL-ISHLAH: Jurnal Pendidikan, 2023)
Civic education aims to foster a respectable national civilization. Civic disposition is character, attitude, or citizenship character in civics education. Therefore, this research aims to provide civic education learning by narrating the civic disposition of the Maluku ethnicity in fighting for and defending the Unitary State of the Republic of Indonesia as well as being material for evaluation of Government policies as a form of effort to maintain the Maluku ethnicity as part of an Indonesian entity. This qualitative research using a purposive sampling technique leads to a descriptive narrative about the civic disposition of the Maluku ethnicity in the narrative of Indonesian nationalism through observation, interviews, and documentation techniques. The informants in this research are the local government and representatives of the Maluku ethnic group who understand the role of the Maluku ethnic group in Indonesian independence, including the millennial generation in Ambon City, to improve the civic disposition of 7 people. The study's results found that the heroic story of the Maluku Republicans becoming Indonesian is evidence of a civic disposition that fights for Indonesianness in unity, which can be used as learning in civic education. History writes that even though they have lived in underdevelopment for decades, even though they have a strong history of giving birth to Indonesians, the Moluccas continue to prove their nationalism and love for the Indonesian homeland.